Meningkatkan Pengetahuan Kesehatan melalui Permainan Ular Tangga - Wulanyani, Ni Made Swasti (Faculty of Psychology, Universitas Gadjah Mada, 2013)
Many infections such as dengue fever, diarrhea, respiratory infections and worms are caused by poor sanitation and careless behaviors. Prior to making behavioral change, there must be cognitive element to develop knowledge in people. This study used Snakes and Ladders game that was modified to contain health information. The goal of this study was to see the effectiveness of using the game in learning. The subjects of this study were 60 students of VI grade of elementary school in Gianyar, Bali. The first group was given health lecture, while the other group was given the Snakes and Ladders game to play at school break time. The result showed a highly significant difference between the ‘lecture group’ and the ‘game group’ (Mean=2.20; SD=1.56; SEM=0.28; t= 7.71, p